Odpowiedzi

2010-03-29T16:08:20+02:00
E) 3-x=-2x

3=-2x+x
x=3

f) 3x+1/7=2x
1/7=2x-3x
x=-1/7

g) 4x-5=3x-1
4x-3x=-1+5
x=4

h) 4+2x=2+x
4-2=x-2x
2=-x
x=-2

i) 1 3/4+ x= -3 1/4
x=-3 1/4-1 3/4
x=-5

x²=9
x=3
równoważne:

(x+3)(x+3)
1 5 1
2010-03-29T16:10:49+02:00
E) 3-x=-2x
-x+2x=-3
x=3

f) 3x+1/7=2x /*7 (pozbywamy się piętra)
3x+1=14x
3x-14x=-1
-11x=-1

g)4x-5=3x-1
4x-3x=-1+5
x=4

h)4+2x=2+x
2x-x=2-2
x=0

2010-03-29T16:11:12+02:00
E) 3-x=-2x
-x+2x=3
x=3

f) 3x+1/7=2x
3x-2x=-1/7
x=-1/7

g) 4x-5=3x-1
4x-3x=-1+5
x=4

h) 4+2x=2+x
2x-x=2-4
x=-2

i) 1¾+x=-3¼
x=-3¼-1¾
x=-5

x²=9 x*x=9